The human rights-based approach to higher education : why human rights norms should guide higher education law and policy - Kotzmann, Jane (New York, NY : Oxford University Press, 2018)
This work seeks to determine if there is still a place for the human right to higher education in the current international context. It compares and contrasts two general theoretical models that are used to frame higher education policy: the market-based approach and the human rights-based approach. It contributes to an understanding of the likely effectiveness of each approach to higher education provision in terms of teaching and learning. This understanding should enable the development of more improved, sophisticated, and ultimately successful higher education policies.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 5, 2018).
Keywords: Education, Higher -- Law and legislation; Human rights; Law; Laws of specific jurisdictions & specific areas of law